2021
DOI: 10.1016/j.jhin.2021.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors for the isolation of multi-drug-resistant Gram-negative bacteria from critically ill patients with COVID-19

Abstract: Background We investigated the clinical characteristics and risk factors for the isolation of multidrug resistant (MDR) Gram-negative bacteria (GNB) from critically ill COVID-19 patients. Methods We retrospectively matched (1:2) critical COVID-19 patients with one or more MDR GNB from any clinical specimen (cases), with those with no MDR GNB isolates (controls). Results Seventy-eight cases were identified (4.5 per 1,000 ICU days, 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 23 publications
1
51
0
3
Order By: Relevance
“…These findings may raise concerns of overuse of antibiotic therapy and a subsequent contribution to the development of increased bacterial resistance [ 19 , 43 ]. Therefore, further research on co-infections is needed to provide rational antibiotic therapy in the era of the SARS-CoV-2 pandemic [ 48 , 49 ]. It is also important to remember that altered, difficult working conditions and fatigue can cause burnout among HCWs, thereby decreasing commitment to their work and adherence to infection prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may raise concerns of overuse of antibiotic therapy and a subsequent contribution to the development of increased bacterial resistance [ 19 , 43 ]. Therefore, further research on co-infections is needed to provide rational antibiotic therapy in the era of the SARS-CoV-2 pandemic [ 48 , 49 ]. It is also important to remember that altered, difficult working conditions and fatigue can cause burnout among HCWs, thereby decreasing commitment to their work and adherence to infection prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the epidemiology and risk factors of MDROs in COVID-19 patients is very important for establishing strategies to treat COVID-19 and prevent infection by MDROs. Although, several studies reported MDRO isolation and antimicrobial stewardship challenges in patients in COVID-19 [12][13][14] , only few studies have dealt with risk factors of MDRO isolation in patients with COVID-19 15 . Therefore, the aim of this study was to evaluate incidences of and risk factors for isolation of MDROs in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The greater the presence of patient co-morbidities, the more frequent the finding of co-incident infections [125,135]. Gram-negative bacillus infections are associated with increased hospital stay and severe COVID-19 [118,140,[157][158][159][160]. They more often arise either in the respiratory tract, with intravenous access devices, or with genitourinary foci [145,155,156,158,160].…”
Section: The Impact Of Covid-19 On Associated Post-onset Bacterial Infectionsmentioning
confidence: 99%
“…Gram-negative bacillus infections are associated with increased hospital stay and severe COVID-19 [118,140,[157][158][159][160]. They more often arise either in the respiratory tract, with intravenous access devices, or with genitourinary foci [145,155,156,158,160]. Bacteremias tend to be less common but are more likely to be seen with intensive care patients [77,145,156,159,161].…”
Section: The Impact Of Covid-19 On Associated Post-onset Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation